Case Report: Identification of a Novel ODAD3 Variant in a Patient With Primary Ciliary Dyskinesia - Wang, Rongchun; Yang, Danhui; Guo, Ting; Lei, Cheng; Chen, Xu; Kang, Xi; Qing, Jie; Luo, Hong (Frontiers in Genetics, 2021)
Background: CCDC151 encodes a protein of 595 amino acids and contain three highly conserved coiled-coil domains, which is essential for cilia axoneme dynein arm assembly and docking. Primary ciliary dyskinesia (PCD) of CCDC151 deficiency is uncommon. Female infertility in PCD related to CCDC151 variants has not been reported. Methods: Whole-exome and Sanger sequencing were used to identify the disease-causing gene of the patient with PCD in a consanguineous Chinese family. Domain analysis was applied to predict the impact of the variant on CCDC151 protein. Results: The 35-year-old female patient exhibited chronic sinusitis, diffuse bronchiectasis, dextrocardia and infertility. We identified a novel homozygous variant in CCDC151, c.1166_1169dupAGAC, p. (Leu391Aspfs*105) in the PCD patient by exome sequencing and Sanger sequencing. This frameshift variant was predicted to be disease causing by bioinformatics analysis and was also not presented in the current authorized large genetic databases. Conclusions: Our study enriches the genetic spectrum and clinical phenotypes of CCDC151 variants in PCD and provide more evidence for future genetic counseling and gene-targeted therapy for this disease.